Anti-NMDA Receptor Encephalitis During Pregnancy. Issue 26 (July 2015) - Mathis, Stéphane; Pin, Jean-Christophe; Pierre, Fabrice; Ciron, Jonathan; Iljicsov, Anna; Lamy, Matthias; Neau, Jean-Philippe; Mello., Carlos
<x xml:space="preserve">Abstract</x> Abstract Anti-N-methyl-D-aspartate receptor (anti-MMDAR) encephalitis is an immune-mediated encephalitis mainly affecting young women. We describe the case of a 21-year-old woman who developed a classical form of anti-NMDAR encephalitis during the 10th week of gestation. The patient had been treated with methylpredinsolone and intravenous immunoglobulins. Birth history of the child was normal, with normal APGAR score. The clinical symptoms of the patient have improved after a few months. This rare occurrence during pregnancy (only 9 other cases described) presents an opportunity to highlight the importance of making the earliest possible diagnosis of this treatable and potentially reversible encephalitis, and to educate gynecologists, psychiatrists, anesthetists, and neurologists on this potential cause of psychiatric and neurological manifestations during pregnancy.